Phytochrome and Circadian Clocks in Samanea: Rhythmic Redistribution of Potassium and Chloride within the Pulvinus during Long Dark Periods - Satter, Ruth L. (1977)
Previous investigations with the electron microprobe reveal that the movements of Samanea leaflets are correlated with massive redistribution of K within the pulvinus. Evidence is now presented that Cl moves with K, whether plants are in white light or darkness, whether or not the amplitude of free running oscillations has damped, and whether or not the rhythm has been rephased by phytochrome photoconversion. The mid-extensor to mid-flexor ratio of K + Cl is correlated with leaflet angle under all conditions. Total Cl in both inner cortex and motor region is approximately 0.6 as high as K. The stoichiometry between Cl and the migratory fraction of K is close to, but not precisely 1:1 in all regions of the pulvinus, suggesting that other ions or systems may also be involved in the balancing of electrical charges.